Interaksi Fundamental ICR dan DER Terhadap Harga Saham Properti dengan Moderasi BI Rate - Inu Yuwan Fatoni; Mifta Hulaikah; Eryul Mufidah; Aris Zulianto (LPPM Universitas KH A. Wahab Hasbullah, 2026)
The property sector is an industry that is very sensitive to monetary policy, but share price dynamics often show anomalies relative to fundamental indicators in volatile market conditions. The novelty of this research lies in testing the Moderated Regression Analysis (MRA) model to reveal the extent to which monetary policy (BI Rate) is able to moderate the influence of internal financial fundamentals (ICR and DER) on stock prices amidst massive government fiscal intervention. Taking the focus on the property sector on the Indonesia Stock Exchange for the 2020-2024 period, the research sample was determined using a purposive sampling approach which produced 100 observation data. Empirical findings confirm that although the model is tested simultaneously feasible (Sig. 0.025), partially only the Debt-to-Equity Ratio (DER) has a significant negative impact on stock prices. On the other hand, the Interest Coverage Ratio (ICR) and BI Rate do not have a significant direct contribution. The crucial results of this research reveal that the BI Rate failed to play a moderating role, which indicates the existence of a